KEMISKINAN DITINJAU DARI PERPEKSTIF AL-QURAN DAN HADIS - Bayu Tri Cahya (Jurnal Penelitian, 2015)
PROVERTY IN THE PERSPECTIVE OF QUR’AN AND HADITH. This paper aims to explain the poverty of  view of  al- Quran and Hadith. This is because poverty is a global problem and a classic that is always there, and had a very large influence on individual and social life. Poverty is also a major enemy of the Muslims, they are obliged to fight against poverty he suffered. In Indonesia, poverty seems to be a necessity for the Indonesian people, especially Muslims. Irony indeed, poverty persists in the country that supposedly rich in natural resources. Most people understand the comparative poverty, while others look at it from the perspective of  moral and evaluative, and others understand it from a scientific point of  view that has been established. However, Islamic economics can be used as tools to save Muslims from poverty. Islam is not only limited economic alternatives, but the solution of  the system of  capitalism or any economic system which has been hailed by the West.Keywords: Proverty, Economic System, Islamic Economy.Tulisan  ini  bertujuan  untuk  menjelaskan  tentang  kemiskinan dari  pandangan  al-Quran  dan  Hadis.  Ini  karena  kemiskinan 41 adalah problema klasik dan global yang selalu ada, dan memiliki pengaruh sangat besar terhadap kehidupan individu maupun sosial. Kemisikinan juga merupakan musuh besar umat Islam, mereka berkewajiban melawan kemiskinan yang menderanya. Di Indonesia, kemiskinan seolah menjadi suatu keniscayaan bagi masyarakat Indonesia, khususnya umat Islam. Ironi memang, kemiskinan tetap ada di negeri yang konon kaya akan berbagai sumber daya alam. Sebagian orang memahami kemiskinan secara komparatif, sementara yang lain melihatnya dari perspektif  moral dan evaluatif, dan yang lain lagi memahaminya dari sudut ilmiah yang telah mapan. Namun, ekonomi Islam bisa dijadikan tools dalam menyelamatkan umat Islam dari kemiskinan. Ekonomi islam bukan hanya sebatas alternatif, melainkan  solusi dari  sistem  kapitalisme  atau  sistem  ekonomi manapun yang selama ini diagung-agungkan oleh Barat.Kata Kunci: Kemiskinan, Sistem Ekonomi, Ekonomi Islam.